(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Namibia was one of the final African states to gain independence, a political transformation which was the outcome of a decades-long liberation struggle. The global dimension of the struggle has been duly recognised by generations of historians. As a result, archival materials related to this era - as well as the colonial ones preceding it – are to be found all over the world. Through a discussion of relevant archival collections pertaining to Namibian history - though located outside the boundaries of the Republic of Namibia – this article considers the global archival paper trail of Namibian colonisation and decolonisation. We shed light on the origins of various collections located in South Africa, Europe, North America, and beyond in order to reveal the ways in which the utilisation of such global archivalia can shape our understanding of Namibian decolonisation. This applies to government archives, private collections, institutional solidarity collections, as well as those of international organisations. We then delve into some of the promises and pitfalls of the digitisation of archival records, noting issues of ethics and methodology. Ultimately, we hold that historians must balance both internal and external Namibiana archivalia in crafting our arguments about the past, and we must balance both the merits and demerits of the digital turn in historical research.